Self-Concept and Sport Participation in Sixth Grade Basic School Students - Špela Virag; Petra Dolenc (University of Maribor Press, 2016)
The purpose of the study was to examine self-concept in relation to sport participation among basic school children. The sample included 109 sixth grade students of different Slovenian basic schools. The participants completed the Slovenian version of the SelfPerception Profile for Children - SPPC. The results show significant gender differences in some specific components of self-concept. Boys exhibited higher scores in perceived physical appearance and athletic competence, whereas girls exhibited higher levels in perceived behavioural conduct. Mean values show that students, engaged in organized sport practice, reported higher scores in all self-concept subscales than their inactive peers, although significant differences between these two groups were found in perceived scholastic competence and athletic competence. The study offers a detailed insight into the multidimensional self-perceptions of sixth grade basic school students. The results highlight the importance of physical/sports activity in the self-concept development and can be useful in promoting an active lifestyle among youth.